Escola e(m) conflito: saberes construídos e silenciados por professores de português - Bohn, Cristina (Universidade do Vale do Rio do Sinos, 2008)
The present study had the objective to recognize the knowledge about social interaction conflicts built by Portuguese Language professors that work in state public school. The subjects of this research were four docents of Fundamental and High School. The analysis focus in the knowledge built or silenced by educators by living he conflicts at school. The immersion in the field begun in 2006 with the observation of the recreation time, the school’s routine and the pedagogic meetings. The research material is formed by open interviews, realized through the year of 2007, being the data interpreted by the light of French’s Speech Analysis Theory principles. The analysis device was built contemplating provocations about the experience of social interaction at school, the contributions of the Portuguese Language, also the conflict itself. Dimensions like docent knowledge, conflict and the scientific field of Portuguese Language to circumscribe the object, in order to enlarge discussions about their implications to
Keywords: análise de discurso; conflitos; língua portuguesa; saberes docentes; portuguese language; speech analysis; docent knowledge; Ciências Humanas